Staying Relevant in the Google Age: Implementing Vertical Search at the University of Manchester — a Technological and Cultural perspective - Beard, Lorraine; Land, Andy (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
John Rylands University Library at the University of Manchester makes a clear commitment to improving resource discovery in its New Directions strategy. In addition an external review of the Library’s systems portfolio identified a clear need to improve the user experience in finding and accessing information. There are also drivers to ensure better utilisation of the Library’s investment in e-resources, as well as the need for the Library to respond to the question of how libraries continue to stay relevant in the Google age. Taking all these factors into account the Library took a strategic decision in 2010 to implement a vertical search solution and it established a formal project to do so in Summer 2010. The project has involved working in close partnership with a number of key stakeholders from the Library, IT Services, multiple vendors and the academic community and is a good example of the changing way in which libraries need to plan and manage their projects in order to improve and deliver services which address the needs of their users. Effective governance, communication, change and project management have been key to the success of this project and highlights the growing importance of these skills in libraries today. The paper will consider the complex technological issues around integrating data from different sources and using different metadata standards. The project has involved vendors working co-operatively together to enable data to move between systems and different metadata formats, which also presents challenges. The cultural issues involved in implementing vertical search will also be discussed, including a shift in the Library’s internal philosophy towards search, the possible impact on the traditional Library catalogue and associated workflows and the changing user perception of the Library in response to vertical search. The project is an excellent case study in new ways of working for libraries, tackling complex technological issues and remaining focussed on improving user experience. The paper will be of interest to other libraries considering or in the process of improving their library’s resource discovery experience.